Sacred groves and local gods: religion and environmentalism in South India - Kent, Eliza F. (Oxford University Press, 2013)
Introduction: sacred groves and local gods: religious environmentalism in South India -- Fierce gods and dense forest: sacred groves near Madurai -- A road runs through it: changing meanings in Malaiyali sacred groves in Tiruvannamalai district -- Mixing botany and belief: guardian deities and their forests in the Pondicherry region -- Soteriology and stake-holders: the greening of the Auroville plateau 1973-2007 -- Sacrifice and sacrality: sacred grove restoration projects near Chennai